(untitled) (Journal of Hama University, 2024)
The aim of the research is to reveal the reality of applying governance principles in public secondary schools in Hama Governorate and their relationship to achieving competitive advantage from the point of view of public secondary school principals in Hama Governorate, as well as to reveal the significance of the differences between the average scores of the research sample members on the governance and competitive advantage questionnaires due to the academic qualification variable.The descriptive, correlational approach and the questionnaire were used as a tool for collecting data. The research sample consisted of (95)one of the principals of public secondary schools in Hama Governorate, who were chosen randomly. The most important findings of the research are the following: The reality of applying the principles of governance in public secondary schools in Hama Governorate, from the point of view of the research sample, reached a medium degree, and the level of competitive advantage for public secondary schools in Hama Governorate, from the viewpoint of the research sample, reached a medium degree, and there is a statistically significant relationship between applying the principles of governance and achieving the advantage. Competitiveness from the point of view of the research sample members has no statistically significant differences between the averages of the research sample members’ answers to the governance and competitive advantage questionnaires due to one variable or another to the academic qualification variable.